Investigating the impact of breastfeeding difficulties on maternal mental health - Gabrielle Rowles; Joseph Keenan; Nicky J. Wright; Karen Hughes; Rebecca Pearson; Hannah Fawcett; Elizabeth C. Braithwaite (Scientific Reports)
Abstract Many women want to breastfeed but experience breastfeeding difficulties with associated consequences for poor mental health. The aim of the current study was to investigate mother’s perceptions of how breastfeeding difficulties have impacted their mental health, couched within a behaviour change model, to identify intervention targets. Data were collected in October 2023 via an online cross-sectional survey. Participants provided qualitative open-ended responses to describe how they felt that breastfeeding difficulties may have impacted their mental health (N = 1141). Data was analysed using thematic analysis and themes were mapped deductively on to the COM-B model of behaviour change. Mothers were highly motivated to breastfeed, but experienced challenges with psychological capability, physical capability, and social opportunity. Analyses resulted in the identification of the following targets for intervention: (1) education around the realities of what to expect when breastfeeding, (2) support for technical challenges and pain management, and (3) education for healthcare professionals, families and wider society on the importance of supporting breastfeeding mothers who are experiencing breastfeeding difficulties. Interventions targeted at breastfeeding mothers who are experiencing breastfeeding difficulties with associated mental health consequences have the potential to reduce rates of both early breastfeeding cessation and poor maternal mental health in the postnatal period.